PENINGKATAN KETERAMPILAN BERBICARA BAHASA ARAB MELALUI MODEL PEMBELAJARAN INTERAKTIF DI MADRASAH DINIYAH MAMBAUS SHOLIHIN - Halim, Habib Abdul; Farid Qomaruddin (MIYAH : Jurnal Studi Islam, 2025)
Abstract: This research aims to determine the effectiveness of the interactive learning model on Arabic speaking skills at the Mamba'us Sholihin Gresik Islamic Boarding School. This research is Classroom Action Research which consists of 2 cycles with the subject of 20 Islamic boarding school students. Data collection was carried out through pre-test, post-test and observation. The results of the research show that student learning scores in the second cycle experienced a significant increase based on the average student score, where in the first cycle, there were only 3 students with good ratings, reaching around 15%, which then increased to 13 students or around 65% in the second cycle. Apart from that, the number of students, which was initially 8 with a sufficient rating and 9 with a poor rating, in the second cycle increased with a rating of 7 with a sufficient rating or around 35%. In this way, learning Arabic speaking skills using an interactive learning model can make learning more effective.? Keyword: Interactive Learning Model, Maharah al-Kalam, Islamic Boarding School